The fear of COVID-19, health literacy and levels of compliance with prevention measures of adult individuals in Turkey - Gülhan Yiğitalp (Journal of Infection in Developing Countries)
Introduction: It is known that health literacy and fear of COVID-19 are effective in complying with COVID-19 prevention measures. A limited number of studies have shown the relationship between health literacy, fear of COVID-19, and compliance with COVID-19 prevention measures. The purpose of this study is to investigate the fear of COVID-19, health literacy, compliance levels with prevention measures of adult individuals and influential factors.